Hard carbon negative electrode material, preparation method and application thereof

CN118637590BActive Publication Date: 2026-10-09CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410346989.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-26
Publication Date
2026-10-09
Estimated Expiration
2044-03-26

AI Technical Summary

Technical Problem

但是硬碳作为负极材料仍然受到首圈库伦效率低、倍率性能差以及循环性能差等瓶颈的制约,这些性能指标是促进钠离子电池商业化的关键因素

Benefits of technology

[0023]The present invention provides a method for preparing hard carbon anode materials that creatively uses a CO2 laser to focus-treat oxygen-doped hard carbon materials, causing secondary carbonization of the sample and altering the existence form of oxygen functional groups. Simultaneously, it introduces a large number of self-doped defects and pore defects, providing more storage sites for sodium ions. This effectively solves the problems of low sodium ion insertion and extraction efficiency and slow ion diffusion rate in hard carbon materials. By controlling the surface structure of hard carbon materials, the method overcomes the problem of low capacity in existing sodium-ion battery hard carbon anode materials, thereby improving the electrochemical performance of the anode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application provides a hard carbon negative electrode material and a preparation method and application thereof, and relates to the technical field of carbon materials.The preparation method of the hard carbon negative electrode material provided by the application creatively uses laser to treat oxygen-doped hard carbon materials, so that the sample is secondarily carbonized, the existing form of oxygen functional groups is changed, a large number of self-doping defects and closed pores are introduced, and more storage sites of sodium ions are provided, so that the problems of low embedding and de-embedding efficiency and slow diffusion rate of sodium ions existing in the hard carbon material are effectively solved.Through the regulation of the surface structure of the hard carbon material, the problem of low capacity of the hard carbon negative electrode material of the sodium ion battery existing in the prior art is overcome, and the electrochemical performance of the negative electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of carbon materials technology, and in particular to a hard carbon anode material, its preparation method, and its application. Background Technology

[0002] In recent years, renewable and clean energy sources such as wind, tidal, and solar power have been developed. However, due to the discontinuous and unstable nature of these energy sources, large-scale energy storage devices are needed to regulate the energy supply structure and achieve large-scale energy storage. Lithium-ion batteries, as important energy storage devices, have been successfully and widely used in various industries. However, the cost of the raw materials used in lithium-ion batteries—cobalt, copper, and lithium—is rising rapidly, and lithium resources are limited, making it difficult to meet human needs. Sodium-ion batteries, with their low cost, superior low-temperature performance, and advanced safety features, show great potential for large-scale energy storage applications. Therefore, developing low-cost, high-performance electrode materials is key to realizing the commercial application of sodium-ion batteries.

[0003] Given the successful application of carbon materials in lithium-ion batteries, carbon materials are considered a promising candidate for sodium-ion batteries. Among the various emerging carbon anode materials used in sodium-ion batteries, hard carbon (HC) has attracted widespread attention due to its relatively low cost, wide availability, and low sodium intercalation voltage plateau. However, as a negative electrode material, hard carbon is still constrained by bottlenecks such as low first-cycle coulombic efficiency, poor rate performance, and poor cycle performance. These performance indicators are key factors in promoting the commercialization of sodium-ion batteries.

[0004] Therefore, there is an urgent need to develop more effective optimization strategies to improve the sodium storage performance of hard carbon anodes in multiple dimensions, so as to promote the commercial application of sodium-ion batteries based on hard carbon anodes.

[0005] In view of this, the present invention is hereby proposed. Summary of the Invention

[0006] One of the objectives of this invention is to provide a method for preparing a hard carbon anode material and the hard carbon anode material obtained therefrom, so as to at least solve one of the technical problems existing in the prior art.

[0007] The second objective of this invention is to provide an electrode sheet comprising the above-mentioned hard carbon anode material and a method for its preparation.

[0008] A third objective of this invention is to provide the application of the aforementioned hard carbon anode material or electrode sheet in the preparation of sodium-ion batteries.

[0009] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted:

[0010] The present invention provides a method for preparing a hard carbon anode material, comprising: treating oxygen-doped hard carbon material with a CO2 laser to obtain the hard carbon anode material.

[0011] Furthermore, the hard carbon is placed in a plasma cleaner and treated under an oxygen atmosphere to obtain the oxygen-doped hard carbon material.

[0012] Furthermore, the plasma cleaner has a processing power of 100–180W and a processing time of 15–30 minutes;

[0013] Furthermore, the plasma cleaner has a processing power of 150W and a processing time of 20 minutes.

[0014] Furthermore, the power of the CO2 laser for fixed-focus processing is 3-5W, the laser scanning speed is 170-200mm / s, and the height of the laser from the sample surface is 250-280mm.

[0015] Furthermore, the CO2 laser has a focusing power of 3.6W, a laser scanning speed of 187.5mm / s, and a laser height of 261mm above the sample surface.

[0016] The present invention also provides a hard carbon anode material prepared by the above-described preparation method.

[0017] The present invention also provides an electrode sheet comprising the aforementioned hard carbon anode material.

[0018] The present invention also provides a method for preparing the above-mentioned electrode sheet, comprising: preparing a slurry from hard carbon negative electrode material, carbon black and binder, coating it onto a copper foil current collector, drying it and cutting it into sheets to obtain the electrode sheet;

[0019] Preferably, the binder comprises sodium carboxymethyl cellulose;

[0020] Preferably, the mass ratio of the hard carbon anode material, carbon black, and binder is 8:1:1.

[0021] The present invention also provides the application of the above-mentioned hard carbon anode material or electrode sheet in the preparation of sodium-ion batteries.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention provides a method for preparing hard carbon anode materials that creatively uses a CO2 laser to focus-treat oxygen-doped hard carbon materials, causing secondary carbonization of the sample and altering the existence form of oxygen functional groups. Simultaneously, it introduces a large number of self-doped defects and pore defects, providing more storage sites for sodium ions. This effectively solves the problems of low sodium ion insertion and extraction efficiency and slow ion diffusion rate in hard carbon materials. By controlling the surface structure of hard carbon materials, the method overcomes the problem of low capacity in existing sodium-ion battery hard carbon anode materials, thereby improving the electrochemical performance of the anode material.

[0024] This invention provides a strategy for improving the electrochemical performance of existing commercial hard carbon. The process is simple, energy-efficient, green and pollution-free. No chemical reagents are used in the entire process, and no secondary pollution is generated, making it more environmentally friendly. Attached Figure Description

[0025] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0026] Figure 1 This is a schematic diagram illustrating the synthesis of hard carbon (HC) anode material (LOHC) prepared by Plasma and CO2 laser treatment according to an embodiment of the present invention.

[0027] Figure 2 Figures (a) and (b) are SEM images of HC and LOHC, respectively; (c) and (d) are HRTEM images of HC and LOHC, respectively; (e) is a TEM image of LOHC; and (f) and (g) are element surface distribution characterization images of the corresponding regions in Figure (e), representing C and O elements, respectively.

[0028] Figure 3 The structural characterization diagrams of HC and LOHC are shown below; (a), (b) and (c), (d) are XPS characterization diagrams of HC and LOHC, respectively; (e) and (f) are Raman characterization diagrams of HC and LOHC, respectively; (g) is XRD phase characterization diagram of HC and LOHC; and (h) is EPR characterization diagram of HC and LOHC.

[0029] Figure 4The figures show the electrochemical performance of HC and LOHC; (a) is the rate performance of HC and LOHC, (b) is the cycle performance of HC and LOHC, (c) is the CV curve of HC and LOHC, (d) and (e) are the charge-discharge curves of HC and LOHC for the first three cycles, and (f) is the electrochemical impedance spectroscopy of HC and LOHC. Detailed Implementation

[0030] Unless otherwise defined herein, the scientific and technical terms used in conjunction with this invention shall have the meanings commonly understood by one of ordinary skill in the art. The meaning and scope of terms shall be clear; however, in any case of potential ambiguity, the definitions provided herein shall prevail over any dictionary or foreign definitions. In this application, unless otherwise stated, the use of "or" means "and / or". Furthermore, the use of the term "comprising" and other forms is non-limiting.

[0031] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] In view of the current unsatisfactory sodium storage performance of existing hard carbon anodes, this invention aims to propose an efficient and feasible hard carbon modification method, which introduces defects and oxygen elements to effectively improve the rate performance and cycle performance of hard carbon anodes.

[0033] According to one aspect of the present invention, a method for preparing a hard carbon anode material is provided, comprising: treating an oxygen-doped hard carbon material with a CO2 laser to obtain the hard carbon anode material.

[0034] The present invention provides a method for preparing hard carbon anode materials that creatively uses a CO2 laser to focus-treat oxygen-doped hard carbon materials, causing secondary carbonization of the sample and altering the form of oxygen functional groups. Simultaneously, it introduces numerous self-doped defects and pore defects, providing more storage sites for sodium ions. This effectively solves the problems of low sodium ion insertion and extraction efficiency and slow ion diffusion rate in hard carbon materials. By controlling the structure of the hard carbon material, the method overcomes the problem of low capacity in existing sodium-ion battery hard carbon anode materials, thereby improving the electrochemical performance of the anode material.

[0035] In some preferred embodiments, hard carbon is placed in a plasma cleaner and treated in an oxygen atmosphere to obtain the oxygen-doped hard carbon material.

[0036] Introducing oxygen functional groups through plasma cleaning allows these incorporated oxygen-containing functional groups and atoms to act as pinning sites during subsequent carbonization, promoting the formation of closed-cell structures. This significantly improves the material's hydrophilicity and further enhances its defect level, promoting electrolyte penetration. Simultaneously, adjusting the interlayer spacing facilitates insertion and extraction during the charging and discharging of sodium-ion batteries.

[0037] Specifically, the processing power of the plasma cleaner is 100-180W, for example, but not limited to 100W, 110W, 120W, 130W, 140W, 150W, 160W, 170W or 180W, preferably 150W; the processing time of the plasma cleaner is 15-30min, for example, but not limited to 15min, 18min, 20min, 22min, 25min, 28min or 30min, preferably 20min.

[0038] Through extensive experimental verification, the inventors of this invention have demonstrated that by uniformly dispersing hard carbon in a petri dish and treating it with plasma in an oxygen atmosphere to introduce oxygen functional groups, these incorporated oxygen-containing functional groups and atoms can serve as pinning sites during subsequent carbonization, promoting the formation of closed-cell structures. Furthermore, by increasing the content of oxygen functional groups in the hard carbon, the hydrophilicity of the material is significantly improved, and the degree of defect in the material is further enhanced, providing more storage sites for sodium ions and promoting electrolyte penetration and adsorption. Simultaneously, adjusting the appropriate interlayer spacing is beneficial for ion insertion and extraction during the charging and discharging of sodium-ion batteries.

[0039] When preparing oxygen-doped hard carbon materials, oxygen-doped hard carbon materials with improved hydrophilicity can be obtained when the processing power is in the range of 100-180W and the processing time is in the range of 15-30min. When the processing power is 150W and the processing time is 20min, the oxygen-doped hard carbon materials prepared can have higher hydrophilicity and defect degree while saving energy.

[0040] Specifically, the power of the CO2 laser for fixed-focus processing is 3 to 5 W, for example, but not limited to 3 W, 4 W or 5 W, preferably 3.6 W; the laser scanning speed is 170 to 200 mm / s, for example, but not limited to 170 mm / s, 180 mm / s, 190 mm / s or 200 mm / s, preferably 187.5 mm / s; the height of the laser from the sample surface is 250 to 280 mm, for example, but not limited to 250 mm, 260 mm, 270 mm or 280 mm, preferably 264 mm.

[0041] Laser high-temperature treatment causes secondary carbonization of the sample, which changes the existence form of oxygen functional groups and introduces a large number of self-doped defects and closed pores, thereby improving electrochemical performance.

[0042] Meanwhile, when the power of the CO2 laser in fixed-focus processing is between 3 and 5 W, the laser scanning speed is between 170 and 200 mm / s, and the laser height above the sample surface is between 250 and 280 mm, self-doped defects and pore defects can be introduced on the basis of secondary carbonization of the sample, thereby improving electrochemical performance. When the power of the CO2 laser in fixed-focus processing is 3.6 W, the laser scanning speed is 187.5 mm / s, and the laser height above the sample surface is 261 mm, further improvements can be achieved while maintaining energy efficiency.

[0043] According to a second aspect of the present invention, a hard carbon anode material prepared by the above-described preparation method is also provided.

[0044] This hard carbon anode material has high hydrophilicity and high defect degree, providing more storage sites for sodium ions, which can promote the penetration and adsorption of electrolyte, and can effectively improve its electrochemical performance when used as an anode material.

[0045] According to a third aspect of the invention, an electrode sheet comprising the aforementioned hard carbon anode material is also provided.

[0046] The electrode sheet provided by this invention has a high sodium ion capacity and good electrochemical performance, and it has all the beneficial effects of hard carbon anode materials, which will not be elaborated here.

[0047] According to a fourth aspect of the present invention, a method for preparing the above-mentioned electrode sheet is also provided, comprising: preparing a slurry from a hard carbon negative electrode material, carbon black and a binder, coating it onto a copper foil current collector, drying it and cutting it into sheets to obtain the electrode sheet.

[0048] The preparation method is simple and easy to operate, making it suitable for large-scale application.

[0049] Preferably, the binder comprises sodium carboxymethyl cellulose;

[0050] Preferably, the mass ratio of the hard carbon anode material, carbon black, and binder is 8:1:1.

[0051] In some specific embodiments, the hard carbon negative electrode material is mixed with carbon black and sodium carboxymethyl cellulose binder in a ratio of (8:1:1) to form a slurry, which is then coated onto a copper foil current collector and dried in a vacuum oven at 80°C for 12 hours. The resulting electrode sheet is then cut into pieces and can be used as the working electrode.

[0052] According to a fifth aspect of the present invention, based on the beneficial effects of the hard carbon anode material and electrode sheet of the present invention, the present invention also provides the application of the above-mentioned hard carbon anode material or electrode sheet in the preparation of sodium-ion batteries.

[0053] The present invention will be further illustrated by the following examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market.

[0054] Example 1

[0055] This embodiment provides a method for preparing a hard carbon anode material, including the following steps:

[0056] (a) Take 1g of commercial hard carbon (Kureha hard carbon) and distribute it evenly in a petri dish. Then place it in a plasma cleaner and treat it in an oxygen atmosphere. The treatment power is 150W and the treatment time is 20min to obtain oxygen-doped hard carbon material (OHC).

[0057] (b) OHC powder was treated with a CO2 laser in an air atmosphere with a fixed focus. The treatment power was 3.6W, the laser scanning speed was 187.5mm / s, and the height of the laser from the sample surface was 261mm, resulting in laser-treated hard carbon anode material (LOHC).

[0058] Flowchart as follows Figure 1 As shown.

[0059] Example 2

[0060] This embodiment provides a method for preparing a hard carbon anode material, including the following steps:

[0061] (a) Take 1g of commercial hard carbon (Kureha hard carbon) and distribute it evenly in a petri dish. Then place it in a plasma cleaner and treat it in an oxygen atmosphere. The treatment power is 100W and the treatment time is 30min to obtain oxygen-doped hard carbon material (OHC).

[0062] (b) OHC powder was treated with a CO2 laser in an air atmosphere with a fixed focus. The treatment power was 3W, the laser scanning speed was 200mm / s, and the height of the laser from the sample surface was 250mm, resulting in laser-treated hard carbon anode material (LOHC).

[0063] Example 3

[0064] This embodiment provides a method for preparing a hard carbon anode material, including the following steps:

[0065] (a) Take 1g of commercial hard carbon (Kureha hard carbon) and distribute it evenly in a petri dish. Then place it in a plasma cleaner and treat it in an oxygen atmosphere. The treatment power is 180W and the treatment time is 15min to obtain oxygen-doped hard carbon material (OHC).

[0066] (b) OHC powder was treated with a CO2 laser in an air atmosphere with a fixed focus. The treatment power was 5W, the laser scanning speed was 170mm / s, and the height of the laser from the sample surface was 280mm, resulting in laser-treated hard carbon anode material (LOHC).

[0067] Example 4

[0068] This embodiment provides a method for preparing a hard carbon anode material, including the following steps:

[0069] (a) Take 1g of commercial hard carbon (Kureha hard carbon) and distribute it evenly in a petri dish. Then place it in a plasma cleaner and treat it in an oxygen atmosphere. The treatment power is 190W and the treatment time is 12min to obtain oxygen-doped hard carbon material (OHC).

[0070] (b) OHC powder was treated with a CO2 laser in an air atmosphere with a fixed focus. The treatment power was 5.5W, the laser scanning speed was 158mm / s, and the height of the laser from the sample surface was 285mm, resulting in laser-treated hard carbon anode material (LOHC).

[0071] Comparative Example 1

[0072] This comparative example provides a method for preparing a hard carbon anode material, including the following steps:

[0073] Hard carbon powder was treated with a CO2 laser in an air atmosphere with a fixed focus. The treatment power was 3.6W, the laser scanning speed was 187.5mm / s, and the height of the laser from the sample surface was 261mm, resulting in laser-treated hard carbon anode material.

[0074] Comparative Example 2

[0075] This comparative example provides a method for preparing a hard carbon anode material, including the following steps:

[0076] A 0.5M sucrose solution was placed in a 50mL high-pressure hydrothermal reactor and heated at 160℃ for 3.5h. The solution was then washed and filtered with deionized water and ethanol to obtain a black powder, which was dried in a vacuum oven at 60℃. The sample was then calcined at 1300℃ for 2h at a heating rate of 2℃ / min. The resulting sample was denoted as HC. Finally, 50mg of HC was placed in an oxygen plasma cleaner and treated at 50% power for 8min to obtain a hydrophilic hard carbon anode material.

[0077] Examples 5-8

[0078] This embodiment provides an electrode sheet, which is prepared by the following method:

[0079] The hard carbon anode materials prepared in Examples 1 to 4 were mixed with carbon black and CMC binder at a mass ratio of (8:1:1) to form a slurry, which was then coated onto a copper foil current collector and dried in a vacuum oven at 80°C for 12 hours. The slurry was then cut into sheets to obtain electrode sheets.

[0080] Comparative Examples 3-4

[0081] This comparative example provides an electrode sheet prepared by the following method:

[0082] The hard carbon anode materials prepared in Comparative Examples 1 and 2 were mixed with carbon black and CMC binder at a mass ratio of 8:1:1 to form a slurry. The slurry was then coated onto a copper foil current collector and dried in a vacuum oven at 80°C for 12 hours. The slurry was then cut into sheets to obtain electrode sheets.

[0083] Experimental Example

[0084] This experimental example uses the electrode sheets provided in Examples 5-8 and Comparative Examples 3-4 for electrochemical testing. In a glove box under an argon atmosphere, using a sodium sheet as the counter electrode, the positive electrode shell, negative electrode shell, glass fiber separator, sodium sheet, and electrolyte were assembled into a CR 3032 button cell according to the correct operating procedures. The electrolyte used was 1M NaClO4 / DMC:EC:EMC = 1:1:1 Vol% / 5% FEC. After the assembled battery was allowed to stand for 24 hours, constant current charge-discharge tests and rate performance tests were performed in the Xinwei testing system, with a voltage range of 0.01-3.0V. The results are shown in the table below:

[0085]

[0086]

[0087] As a typical example, a comparison was made between the electrode sheet provided in Example 5 and the hard carbon electrode sheet, and the results are as follows: Figures 1-4 As shown:

[0088] Figure 2 (a) and (b) are SEM morphology images of HC, LOHC and LOHC, respectively, indicating that the diameter of hard carbon particles is approximately 10-20 μm. Figure 2 (c) and (d) are HRTEM images of HC and LOHC, respectively. The images show that after processing, the lattice fringes of LOHC become relatively long-range ordered, the carbon interlayer spacing increases, the degree of graphitization increases, and a structure surrounded by multiple parallel carbon layers is formed, which is beneficial for sodium storage. Figure 2In Figure (f) and (g), the elemental distribution maps for the corresponding regions in (e) are shown, representing C and O elements respectively. The elemental distribution maps show that oxygen is uniformly distributed on the hard carbon surface, proving that Plasma treatment can successfully dope oxygen into hard carbon.

[0089] Figure 3 Figures (a) and (c) show XPS phase characterization diagrams of the C1s orbitals of HC and LOHC, respectively, with four peaks corresponding to C=C, C=C, CO, and C=O. Figures (b) and (d) show XPS phase characterization diagrams of the O2s orbitals of HC and LOHC, respectively, with three peaks corresponding to C=O, CO, and COO. The comparison shows that after surface modification, the oxygen content of hard carbon increases, and the oxygen content is mainly in the form of C=O, which is beneficial for providing more Na. + The active sites are improved to enhance the electrochemical performance of sodium-ion batteries. Figure 3 (e) and (f) are Raman peak diagrams of HC and LOHC, respectively. By comparing the ID / IG values, it can be seen that the graphitization degree of LOHC is higher than that of HC, and the degree of disorder is lower. Figure 3 (g) in the figure is the XRD characterization of HC and LOHC. The sample showed broad peaks at 24° and 43°, corresponding to the (002) and (100) crystal planes of hard carbon, respectively. According to the Bragg equation, the d(002) interlayer spacing values ​​of HC and LOHC were calculated to be 0.385 and 0.381 nm, respectively. This result is consistent with the measurement results of the TEM image. Figure 3 (h) in the figure represents the EPR characterization of HC and LOHC, demonstrating that LOHC has higher defects compared to HC.

[0090] Figure 4 (a) shows the rate performance comparison curves of the half-cells assembled from HC and LOHC samples at different current densities. LOHC has a higher rate capacity than HC at all current densities, demonstrating excellent rate performance. Figure 4 (b) shows the half-cell assembled from HC and LOHC samples at 30 mAg. -1 A comparison of cycling performance at current density shows that the LOHC can output 315mAh g after 100 cycles. -1 The reversible specific capacity, while HC only outputs 244mAh g. -1 Reversible specific capacity. Figure 4 (c) in the figure represents the CV curves of the first two cycles for HC and LOHC materials, with a scan rate of 0.1 mV / s. -1The scanning range was 0-3V. The area under the CV curve of LOHC was larger than that of HC, indicating that LOHC has a higher reversible specific capacity; the reversible redox peak at 0.01–0.1V is attributed to Na+ in the graphite layer or nanopores. + Insertion / extraction corresponds to the plateau region of the GCD curve, and the redox peak at 0.6V is Na. + The result of the redox reaction with C=O. Figure 4 (d) and (e) in the figure represent HC and LOHC at 30 mAg, respectively. -1 The GCD curves for the first three cycles at current density clearly show that the reversible capacity of LOHC is higher than that of HC. Figure 4 (f) in the figure is the impedance diagram of HC and LOHC materials, which shows that LOHC has a smaller charge transfer resistance and a faster ion transport rate.

[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a hard carbon anode material, characterized in that, include: Hard carbon is placed in a plasma cleaner and treated under an oxygen atmosphere to obtain oxygen-doped hard carbon material. Then, the oxygen-doped hard carbon material is treated with a CO2 laser to obtain the hard carbon anode material.

2. The preparation method according to claim 1, characterized in that, The plasma cleaner has a processing power of 100~180W and a processing time of 15~30 min.

3. The preparation method according to claim 2, characterized in that, The plasma cleaner has a processing power of 150 W and a processing time of 20 min.

4. The preparation method according to claim 1, characterized in that, The CO2 laser used for fixed-focus processing has a power of 3~5W, a laser scanning speed of 170~200 mm / s, and a laser height of 250~280 mm above the sample surface.

5. The preparation method according to claim 4, characterized in that, The CO2 laser used for fixed-focus processing has a power of 3.6W, a laser scanning speed of 187.5 mm / s, and a height of 261 mm above the sample surface.

6. Hard carbon anode material prepared by the preparation method according to any one of claims 1 to 5.

7. An electrode sheet, characterized in that, Including the hard carbon anode material as described in claim 6.

8. The method for preparing the electrode sheet according to claim 7, characterized in that, include: Hard carbon anode material, carbon black and binder are mixed into a slurry, which is then coated onto a copper foil current collector. After drying, the slurry is cut into sheets to obtain the electrode sheet.

9. The method for preparing the electrode sheet according to claim 8, characterized in that, The binder includes sodium carboxymethyl cellulose.

10. The method for preparing the electrode sheet according to claim 8, characterized in that, The mass ratio of the hard carbon anode material, carbon black, and binder is 8:1:

1.

11. The application of the hard carbon anode material of claim 6 or the electrode sheet of claim 7 in the preparation of sodium-ion batteries.

Citation Information

Patent Citations

  • Novel solid laser of graphene quantum dot-doped gallium oxide crystal

    CN109346914A

  • Carbon dioxide laser superhard film

    CN215560681U